The submicroscopic level of chemistry: Analyzing learning objects to help the teacher in the process of teaching and learning - Figueiredo, Marcia Camilo; De Souza, Aguinaldo Robinson [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Many knowledge covered in the discipline of chemistry, especially the submicroscopic level, require teachers to use didactic resources to assist them during the process of teaching and learning. In view of this concern, the study investigated whether licentiate in chemistry can illustrate in design and understand the concept of randomness present in the Kinetic Theory of Gases, during the application of didactic objects. In order to achieve this goal, we seek to answer the central problem of the study: does the participants take into consideration the experiences in each proposed context in the learning objects to redraft the drawings and scientifically understand the concept of randomness? For analysis of the drawings, a standard was built from the figures of didactic objects. The data revealed that every new experience, some participants sometimes sought in their previous schemes, assimilate the facts observed in the context of application of learning objects, and sometimes built new schemes by modifying the way to illustrate the particles in the drawings. We conclude that learning objects can be used as digital resources in pedagogical practices of teachers, contributing to the teaching and learning of the scientific concept of randomness present in the kinetic theory of gases.
Keywords: kinetic theory of gases; randomness; teaching and learning chemistry